2023
DOI: 10.1088/2631-7990/aca79f
|View full text |Cite
|
Sign up to set email alerts
|

High efficiency GHz laser processing with long bursts

Abstract: Bursts of GHz repetition rate pulses can significantly increase the ablation efficiency of femtosecond laser material processing.. Ablation by GHz repetition rate bursts of femtosecond pulses is a multi-step process, consisting of a first thermal incubation phase, followed by a highly efficient ablation phase. GHz ablation therefore combines thermal and non-thermal ablation mechanisms. With an optimal choice of the burst duration, the ablation efficiency can be highly enhanced. Long bursts, comprising tens to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…where Imχ 3 is the imaginary part of the third order optical susceptibility, c is the ve The NLO performance is characterized by the optical setup in Figure 5. The laser and optical instrument parameters can be found in Section 3.4 on characterization.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…where Imχ 3 is the imaginary part of the third order optical susceptibility, c is the ve The NLO performance is characterized by the optical setup in Figure 5. The laser and optical instrument parameters can be found in Section 3.4 on characterization.…”
Section: Resultsmentioning
confidence: 99%
“…where Imχ (3) is the imaginary part of the third order optical susceptibility, c is the velocity of light, n 0 is the linear refraction, and ω is the angular frequency of light. The nonlinear absorption coefficients and the imaginary parts of third-order NLO susceptibilities are calculated through fitted values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the temporal sequence of the energy distribution onto the material can be flexibly modified. Audouard et al [6] have tested in an experimental campaign different pulse repetition rates with a burst rate settled at 100 kHz. Their findings showed that by increasing the fluence of the burst and the burst duration, the ablation depth increases.…”
Section: Introductionmentioning
confidence: 99%